Teaching and Learning (T&L) among university students during the Movement Control Order (MCO) / Nor Hamiza Mohd Ghani, Sholehah Abdullah and Mohd Khairi Ismail - Mohd Ghani, Nor Hamiza; Abdullah, Sholehah; Ismail, Mohd Khairi (Universiti Teknologi MARA, Perlis, 2021)
Both academic institutions and schools were required to conduct online learning during the Movement Control Order (MCO) period. This study aims to identify Universiti Teknologi Mara (UiTM) Terengganu's branch students' perceptions of teaching and learning (T&L) during MCO. The preferred technology framework for T&L during the MCO period is also identified in this report. Furthermore, this study identifies the factors that influenced the choice of said application. The respondents were 256 UiTM Terengganu students from eight specialisations. Data were gathered through the use of online questionnaires administered through Google Forms. According to the findings, students had a generally positive attitude toward the online learning process but were less satisfied with its effectiveness. In terms of application selection, the university's teaching and learning platform, the U-Future system, comes in first, followed by Google Classroom, Telegram, and WhatsApp. This study also discussed the strategies for improving the effectiveness of technology utilisation to optimise e-learning.